Corrigendum to “A new predictive model for a photovoltaic module's surface temperature” [Energy Rep. 8 (2022) 15206–15220, (S2352484722024805), (10.1016/j.egyr.2022.11.094)] - Silva, Domisley Dutra [UNESP]; Marson, Vinicius [UNESP]; de Souza, Reinaldo Rodrigues; de Oliveira, Jeferson Diehl; Silva, João Batista Campos [UNESP]; Cardoso, Elaine Maria [UNESP] (Elsevier, 2024)
The authors regret to inform you that in the refereed paper, Eq. (8) and the values of constants a and b were incorrectly written during manuscript revision before publication. Eq. (8) should be: [Formula presented] And the values of constants [Formula presented] and [Formula presented] should be 17.27 e 237.15, respectively. We are sorry for this writing mistake and highlight that this adjustment does not affect the interpretation of the data or any discussions in the manuscript. The authors would like to apologize for any inconvenience caused.